Development Of Cognitive Processes In Students as An Important Factor of Intellect Formation - Ashurov Ramzidin Ramazonovich (Indonesian Journal Publisher, 2025)
In this article, in the intellectual formation of elementary school students, the ability to form several ideas at the same time, the ability to find several solutions to a problem, and the ability to concentrate thoughts on an object are harmoniously manifested, the priority of attention concentration proven to have an effect. The study of students' intellectual development is one of the important factors in the modern education system. The parallel development of cognitive processes with the intellectual development of students plays an important role in ensuring the intellectual maturity of the student.